"Beaned": A 5‐Year Analysis of Baseball‐Related Injuries of the Face. (9th September 2015) - Carniol, Eric T.; Shaigany, Kevin; Svider, Peter F.; Folbe, Adam J.; Zuliani, Giancarlo F.; Baredes, Soly; Eloy, Jean Anderson
Abstract : Objectives: Baseball remains one of the most popular and safest games played by children and adults in America and worldwide. Rules and equipment changes have continued to make the game safer. For youth leagues, pitching restrictions, safety balls, helmets, and face mask equipment continue to make the game safer. With increased utilization of safety equipment, the objective was to analyze recent trends in baseball‐related facial injuries. Study Design: Cross‐sectional analysis of a national database. Methods: The National Electronic Injury Surveillance System was searched for baseball‐related facial injuries with analysis of incidence, age, and sex and specific injury diagnoses, mechanisms, and facial locations. Results: From 2009 to 2013, there were 5270 cases entries, or 187, 533 estimated emergency department (ED) visits, due to baseball‐related facial injuries. During this time, there was a significant decline in the incidence of ED visits ( P =. 014). Inclusion criteria were met by 3208 visits. The majority of injuries occurred in patients ≤18 years old (81.5%). The most common injury was laceration (33.2%), followed by contusion (29.7%) and fracture (26.9%), while the most common injury site on the face was the nose (24.9%). The injuries were most commonly due to impact from a baseball (70%) or a bat (12.5%). Conclusion: The overall incidence of ED visits due to baseball‐related facial injuries has decreased over the past 5 years, concurrent with increased societal use of protective equipment. Nonetheless, these injuries remain a common source for ED visits, and a continued effort to utilize safety measures should be made, particularly in youth leagues.